2022
DOI: 10.7554/elife.74062
|View full text |Cite
|
Sign up to set email alerts
|

Fast bacterial growth reduces antibiotic accumulation and efficacy

Abstract: Phenotypic variations between individual microbial cells play a key role in the resistance of microbial pathogens to pharmacotherapies. Nevertheless, little is known about cell individuality in antibiotic accumulation. Here, we hypothesise that phenotypic diversification can be driven by fundamental cell-to-cell differences in drug transport rates. To test this hypothesis, we employed microfluidics-based single-cell microscopy, libraries of fluorescent antibiotic probes and mathematical modelling. This approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 112 publications
3
56
2
Order By: Relevance
“…One of the most prevalent microfluidic single-phase designs for microbiology is the mother machine, 102 which has been used on numerous occasions to study bacteria in an antibiotic context or close to it: e.g., mother machine was used for the analysis of mutation frequency in E. coli, 103 for studying viable but non-culturable bacteria during antibiotic treatment, 104 for describing the accumulation of polar multidrug efflux pumps that grant antibiotic resistance in older cells and less so in daughter cells, 105 for studying bacterial persistance, 106,107 uptake and efflux of antibiotics by bacteria 108 with fluorescently labelled antibiotics, 109 and measuring the efficacy of bacteria clearance with phages. 110,111 The basic mother machine consists of a large main channel through which growth medium flows and of multiple shallow and narrow dead-end channels that are perpendicular to the main channel, forming a comb-like structure.…”
Section: Microfluidic Flow Chambers For Quantitative Astmentioning
confidence: 99%
“…One of the most prevalent microfluidic single-phase designs for microbiology is the mother machine, 102 which has been used on numerous occasions to study bacteria in an antibiotic context or close to it: e.g., mother machine was used for the analysis of mutation frequency in E. coli, 103 for studying viable but non-culturable bacteria during antibiotic treatment, 104 for describing the accumulation of polar multidrug efflux pumps that grant antibiotic resistance in older cells and less so in daughter cells, 105 for studying bacterial persistance, 106,107 uptake and efflux of antibiotics by bacteria 108 with fluorescently labelled antibiotics, 109 and measuring the efficacy of bacteria clearance with phages. 110,111 The basic mother machine consists of a large main channel through which growth medium flows and of multiple shallow and narrow dead-end channels that are perpendicular to the main channel, forming a comb-like structure.…”
Section: Microfluidic Flow Chambers For Quantitative Astmentioning
confidence: 99%
“…This indicates that while cells can reliably sense the onset of H2O2 stress and respond rapidly, the response magnitude depends on an unidentified factor that varies substantially between cells. This heterogeneity could be caused by a variety of mechanisms, including molecular stochasticity in the specific regulatory circuits or general gene expression machinery (Golding et al, 2005;Uphoff et al, 2016), cell-to-cell variation in growth or morphology (Łapińska et al, 2022;Ojkic et al, 2022;Sampaio et al, 2022) , variable cellto-cell interactions (Dal Co et al, 2020;Snoussi et al, 2018;van Gestel et al, 2021), or differences in the local environment of cells (Snoussi et al, 2018;van Vliet et al, 2018). To pinpoint the mechanisms, we designed a machine learning model using random forest regression [Figure 2A].…”
Section: Machine Learning Model Predicts Single-cell Responses To H2o2mentioning
confidence: 99%
“…Variation in cell growth and morphology can also affect the influx, dilution, and reaction-diffusion dynamics of stressor molecules such as ROS (Łapińska et al, 2022; Ojkic et al, 2022; Sampaio et al, 2022). Furthermore, cells in a population can interact and modulate their environment in response to stress (Dal Co et al, 2020; Snoussi et al, 2018; van Gestel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of fluorescent probes derived from antimicrobial substances to study drug susceptibility in single bacterial cells has recently been demonstrated for a range of antibiotics 22,23 . Here we demonstrate that this approach is also promising for BACs and related QACs, which are used as disinfectants, antiseptics, and preservatives 1 .…”
Section: Common Mode Of Action In Bac and Nbd-ddamentioning
confidence: 99%